Psikoedukasi Menabung Sampah pada Siswa Kelas 4 SD Unggulan Puri Taman Sari - Kurniati Zainuddin; Adelia Magfiratul Maula; Aldawiah Aldawiah; Nurul Azizah Futri As (Universitas Negeri Makassar, 2024)
Waste has always been a problem that until now has not yet found the best solution. Until now, the behavior of public concern for waste is still very low. Based on these problems, it is important to carry out psychoeducation from an early age about waste sorting and how to save waste so that knowledge about waste processing increases. The method for analyzing the results of this psychoeducation is to use a quantitative method. Before and after the psychoeducation was carried out, participants were given a pre-test and post-test using a scale that aims to measure the extent to which participants understand the material presented by the researcher. Based on the results of the data analysis carried out, it was found that the psychoeducation carried out was able to increase understanding of the definition of waste, the impact of unprocessed waste, sorting waste based on the type of waste, and how to save at a waste bank.